Frequency of self-oscillations - Groszkowski, Janusz (Pergamon Press, 1964)
Frequency of Self-Oscillations covers the realm of electric oscillations that plays an important role both in the scientific and technical aspects. This book is composed of nine chapters, and begins with the introduction to the alternating currents and oscillation. The succeeding chapters deal with the free oscillations in linear isolated systems. These topics are followed by discussions on self-oscillations in linear systems. Other chapters describe the self-oscillations in non-linear systems, the influence of linear elements on frequency of oscillations, and the electro mechanical oscillato.